Washback of a High-stakes Language Exam on Spanish Teachers' Practice in Brazil - Yasser Abdullah Al Tamimi; Gladys Quevedo-Camargo; Rafael Sena Raposo de Melo (Journal of Linguistics and Language Teaching)
Abstract (English)